As-doped SnSe single crystals: Ambivalent doping and interaction with intrinsic defects - Čermák Šraitrová, Kateřina; Cizek, J; Holy, V; Kašparová, Jana; Plecháček, Tomáš; Kucek, Vladimír; Navrátil, Jiří; Krejčová, Anna; Drašar, Čestmír (American Physical Society, 2021)
We performed ambivalent doping study on single crystals of two sets, SnSe1-xAsx and Sn1-xAsxSe, with the aim to explore the interaction of doping species with intrinsic defects. We found that As atoms substitute preferentially for Se atoms in both sets forming the extrinsic substitutional point defect As-Se. In the first set, As lowers the concentration of Sn vacancies, V-Sn, by an order of magnitude compared to undoped stoichiometric SnSe crystal. The remaining Sn vacancies are preferentially coordinated with As atoms. Importantly, a very low concentration of As led to healing process of hosting structure in terms of intrinsic point defects and eventual SnSe2 inclusions. This is reflected in an increase of the Hall mobility and drop of the Hall concentration. In the second set, the concentration of Sn vacancies markedly increases upon doping in contrast to the first set. Additionally, the coordination of Sn vacancies by As atoms is less evident due to the high concentration of vacancies. The substitutional defect As-Se is a deep-level defect that produces no free carriers at room temperature. Moreover, the coupling of V-Sn to As-Se defects increases their activation energy. This results in an unprecedentedly low Hall concentration in SnSe which stays below 10(16) cm(-3) for x = 0.0075. The present study indicates that doping of SnSe is a rather complex process that generally includes a strong interaction of doping atoms with the hosting structure. On the other hand, such doping allows adjustment of the type and concentration of defects. The present study reveals a general tendency of point defects to clustering, which modifies the properties of point defects markedly.
Monokrystaly SnSe dopované arsenem: Ambivalentní dopování a interakce s intrinsickými defekty
Keywords: SnSe; single crystals; As; ambivalent doping; SnSe; monokrystaly; As; ambivalentní dopování